2017
DOI: 10.24953/turkjped.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of weight estimation methods and evaluation of usability of Broselow Luten tape in Turkish children

Abstract: It is controversial which method is more reliable for weight estimation of a child in an emergent situation. The aim of this study is to compare different methods and to review the applicability of Broselow Luten tape for Turkish children. This study was performed prospectively in patients presenting to pediatric emergency department. Weight estimation of patients were performed by parent, physician, nurse and Broselow Luten tape. Finally actual weight and height of the patient were measured. A total of 438 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This study demonstrated a good correlation between the weight estimated by the BT and the actual weight of the children up to 6 years. Varghese et al [13] in India and Gultekingil-keser et al [14] in Turkey equally documented a good correlation of the Broselow tape with actual weight measurements in children. This however was not the case in the index study for children who were more than 6 years (or weighed >25kg) as their weights were overestimated with a mean percentage error of greater than 5% compared to less than 5% in younger ones.. Al Sulaibkh et al [15] and Alharbi [16] and colleagues, both in Saudi Arabia observed similar occurrences that at weights of study participants of 26 kg and above, the Broselow tape overestimated the weights of the children.…”
Section: Discussionmentioning
confidence: 98%
“…This study demonstrated a good correlation between the weight estimated by the BT and the actual weight of the children up to 6 years. Varghese et al [13] in India and Gultekingil-keser et al [14] in Turkey equally documented a good correlation of the Broselow tape with actual weight measurements in children. This however was not the case in the index study for children who were more than 6 years (or weighed >25kg) as their weights were overestimated with a mean percentage error of greater than 5% compared to less than 5% in younger ones.. Al Sulaibkh et al [15] and Alharbi [16] and colleagues, both in Saudi Arabia observed similar occurrences that at weights of study participants of 26 kg and above, the Broselow tape overestimated the weights of the children.…”
Section: Discussionmentioning
confidence: 98%